Assessing relative biomarker responses in marine and freshwater bivalve molluscs following exposure to phosphorus 32 (32P): Application of genotoxicological and molecular biomarkers. (March 2020) - Vernon, Emily L.; Bean, Tim P.; Jha, Awadhesh N.
Abstract: Anthropogenic radionuclides can enter water bodies through accidental or controlled discharges. In order to assess their potential impact, understanding the link between exposure, tissue specific bioaccumulation and radiation dose rate, to biological or biomarker responses in aquatic biota is required. Adopting an integrated, multi-biomarker, multi-species approach, we have investigated potential biological responses induced by short-lived radionuclide, phosphorus-32 ( 32 P, radiophosphorus) in two ecologically important mussel species, the freshwater Dreissena polymorpha (DP) and marine Mytilus galloprovincialis (MG). Adult individuals were exposed to 32 P for 10 days, to acquire nominal whole-body average dose rates of 0.10, 1 and 10 mGy d −1, which encompass a screening value of 10 μGy h −1 (0.24 mGy d −1 ), in accordance with the ERICA tool. Following exposure, a suite of genotoxic biomarkers (DNA damage, γ-H2AX induction and micronucleus [MN] formation) were measured in gill and digestive gland tissues, along with transcriptional expression of selected stress-related genes in both the species (i.e. hsp70/90, sod, cat and gst ). Our results demonstrate the relationship between tissue specific dosimetry, where 32 P induced a dose-dependent increase, and biological responses independent of species. Gene expression analysis revealed little significant variation across species or tissues. Overall, MG appeared to be more sensitive to short-term damage (i.e. high DNA damage and γ-H2AX induction), particularly in digestive gland. This study contributes to limited knowledge on the transfer and biological impact of radionuclides within differing aquatic systems on a tissue specific level, aiding the development of adequate management and protective strategies. Highlights: Multi-biomarker approach to investigate 32P-induced responses in bivalves. ERICA tool used to determine whole body and tissue specific radiation dose. Marine mussels showed higher sensitivity for comet and gamma-H2AX induction. Freshwater mussels showed higher sensitivity for micronucleus induction. Expression of oxidative stress related genes not correlated with genotoxicity.